Implantable cardioverter-defibrillators in the elderly: rationale and specific age-related considerations - Barra, Sérgio (2016)
Despite the increasingly high rate of implantation of cardioverter-defibrillators (ICD) in elderly patients, data supporting their clinical and cost-effectiveness in this age stratum are ambiguous and contradictory. We comprehensively reviewed the state-of-the-art data regarding the applicability, safety, clinical- and cost-effectiveness of the ICD in elderly patients, and analysed which patients in this age stratum are more likely to get a survival benefit from this therapy. Although peri-procedural risk may be slightly higher in the elderly, this procedure is still relatively safe in this age group. In terms of correcting potentially life-threatening arrhythmias, the effectiveness of ICD therapy is comparable in older and younger individuals. However, the assumption of persistent ICD benefit in the elderly population is questionable, as any advantage of the device on arrhythmic death may be largely attenuated by a higher total non-arrhythmic mortality. While septuagenarians and octogenarians have higher annual all-cause mortality rates, ICD therapy may remain effective in highly selected patients at high risk of arrhythmic death and with minimum comorbidities despite advanced age. ICD intervention among the elderly, as a group, may not be cost-effective, but the procedure may reach cost-effectiveness in those expected to live >5-7 years after implantation. Biological age rather than chronological age per se should be the decisive factor in making a decision on ICD selection for survival benefit.